2017
DOI: 10.1097/mcp.0000000000000418
|View full text |Cite
|
Sign up to set email alerts
|

Innovating cystic fibrosis clinical trial designs in an era of successful standard of care therapies

Abstract: Purpose of review Evolving cystic fibrosis (CF) ‘standards of care’ have influenced recent CF clinical trial designs for new therapies; care additions/improvements will require innovative trial designs to maximize feasibility and efficacy detection. Recent findings Three CF therapeutic areas (pulmonary exacerbations, Pseudomonas aeruginosa airway infections, and reduced CF Transmembrane Conductance Regulator [CFTR] protein function) differ with respect to the duration for which recognized ‘standards of care’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Validated surrogate endpoints may be used if they are strongly associated with direct clinical endpoints. Growth has been used in the past as a validated surrogate endpoint, though not in any recent drug trials 35,37 . As CFTR modulator studies expand to younger populations, linear growth may be affected and may again become an outcome of interest 34,38 .…”
Section: Clinical Developmentmentioning
confidence: 99%
“…Validated surrogate endpoints may be used if they are strongly associated with direct clinical endpoints. Growth has been used in the past as a validated surrogate endpoint, though not in any recent drug trials 35,37 . As CFTR modulator studies expand to younger populations, linear growth may be affected and may again become an outcome of interest 34,38 .…”
Section: Clinical Developmentmentioning
confidence: 99%
“…An additional challenge is the design of CF gene therapy trials in the age of highly effective modulator therapies, when discontinuation of those therapies may not be possible, and simple placebo controls are unlikely to be acceptable. 50 Finally, for the first trials using integrating vectors or gene-editing agents that can target the airway stem cells, the patient population requires additional thought, as it is possible that only patients with advanced disease will be eligible, due to the unknown long-term effects of the therapy.…”
Section: Lung Genetic Therapies Require New Outcome Assessment Technimentioning
confidence: 99%
“…An example would be a non-inferiority study, which is designed to show that a new therapy is not unacceptably worse than current standard therapy. This situation may arise in CF when comparing a new drug within the same therapeutic class (e.g., CFTR modulator or new inhaled antibiotic) to an established drug when comparison with a placebo would not be acceptable (42). Clinician surveys have indicated that many are uncomfortable withdrawing efficacious medications (43).…”
Section: Clinical Trial Endpointsmentioning
confidence: 99%